Karnawał – największe party świata Andrzeja Fidyka jako widowisko pełne kontrastów - Fiołek-Lubczyńska, Bogumiła (Wydawnictwo Wydziału Nauk Społecznych Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
In this documentary A. Fidyk is an anthropologist equipped with a film camera. He presents Rio during the carnival as a space of cultural and social diversity. Rio is visibly replete with social contrasts: the extreme poverty of the homeless exists alongside the luxury of the bicheiros. While some die of poverty – as the film’s narrator states – others die of fear. However, everyone is equal within the cultural dimension of the carnival, during the Samba Schools Parades at the Rio Sambadrome, occurring three days before Ash Wednesday. In his documentary Fidyk depicts a spectacle which is deeply rooted in tradition; as an explorer of culture, he draws the viewer’s attention to this culture’s unifying features.
Keywords: widowisko kulturowe; proces rytualny; antystruktura; Andrzej Fidyk